Reasonable accommodation, career development, and psychological well-being: autoethnography as a method of qualitative research - Gulyamova, Saodat Tolibovna; Jamiah Manap; Aizan Sofia Amin; Nik Hairi Omar (Penerbit Universiti Kebangsaan Malaysia, 2024)
Individuals with health issues and disabilities tend to encounter difficulties in the workplace, including decreased productivity and lower job performance compared to those without such problems. Nevertheless, creating a workplace environment that accommodates individuals with disabilities can help them overcome workplace obstacles and fulfil their job duties at the same level as disability-free individuals. Providing reasonable accommodation is one practical step in establishing an inclusive environment for those with vision impairments, leading to career development and psychological well-being. This paper focuses on workplace-related autoethnographic stories to explore the fundamental aspects of reasonable accommodation, career development, and psychological well-being for individuals with vision impairments. This study employed the method of autoethnography in qualitative research. Autoethnographic data was collected through personal reflection and the collection of relevant artefacts. Thematic analysis was used for the data analysis procedure. Therefore, having a disability does not necessarily mean an individual cannot do their job to the necessary standard. Visually impaired individuals can excel in their careers and attain psychological well-being when they are part of a workplace environment that is accommodating to their needs. To enhance job performance, career goals, and psychological well-being among employed disabled individuals, it is necessary to define "reasonable accommodation" in the Law of the Republic of Uzbekistan on the Rights of Persons with Disabilities, based on the UN Convention.